Structural constraints and dynamics of bacterial cell wall architecture - de Pedro, Miguel A.; Cava, Felipe (Frontiers in Microbiology, 2015)
The peptidoglycan wall (PG) is a unique structure which confers physical strength and defined shape to bacteria. It consists of a net-like macromolecule of peptide interlinked glycan chains overlying the cell membrane. The structure and layout of the PG dictates that the wall has to be continuously modified as bacteria go through division, morphological differentiation and adaptive responses. The PG is poorly known in structural terms. However, to understand morphogenesis a precise knowledge of glycan strand arrangement and of local effects of the different kinds of subunits is essential. The scarcity of data led to a conception of the PG as a regular, highly ordered structure which strongly influenced growth models. Here, we review the structure of the PG to define a more realistic conceptual framework. We discuss the consequences of the plasticity of murein architecture in morphogenesis and try to define a set of minimal structural constraints that must be fulfilled by any model to be compatible with present day information.